Online learning platform – a bibliometric review of the literature & research frontier - Feh, Irene Khor Yeow; Kheng, Yeoh Khar; Jaganathan, Mathivannan (Edelweiss Applied Science and Technology, 2025)
The primary objective of this research is to trace the development of studies on online learning platforms (OLP) in the digital era. It provides a comprehensive bibliometric mapping of OLP articles published in globally recognized sources, offering detailed metadata analysis. The study pursues three main goals: first, to investigate the overall body of OLP literature; second, to outline the key characteristics of OLP-related publications; and third, to identify the main research areas within the field. Bibliometric analysis was conducted using VOSviewer and Biblioshiny, a Shiny application integrated with the Bibliometrix R package. These tools processed and visualized data retrieved from the Scopus database. The dataset included publications from 2003 to August 2023, refined through careful screening and validation. Findings provide significant insights into the evolution and current state of OLP research, highlighting frequently cited works, prolific authors, active countries, key sources, and keyword trends. Additionally, co-occurrence networks and thematic mapping reveal intellectual and conceptual structures in the domain. This study underscores both current and emerging directions in OLP research. Future work should extend the scope beyond Scopus by incorporating databases such as Web of Science and IEEE Xplore, while also encouraging broader international collaborations and thematic diversity.